2015
DOI: 10.1167/iovs.15-16563
|View full text |Cite
|
Sign up to set email alerts
|

Roles of Epithelial Cell–Derived Type 2–Initiating Cytokines in Experimental Allergic Conjunctivitis

Abstract: Among the type 2-initiating cytokines, IL-33 may play a major role in conjunctival inflammation in an RW-EAC model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 34 publications
1
21
0
Order By: Relevance
“…Our results showed the indispensable roles of IL‐33 and TSLP in the eosinophil infiltration induced by papain‐CL, this result is consistent with previous reports showing attenuated papain‐induced allergic airway inflammation in IL‐33 KO mice , and reduced papain‐induced allergic inflammation in the lung of TSLPR KO mice . In the case of ragweed induced experimental allergic conjunctivitis, we evaluated clinical scores (lid edema, conjunctival hyperemia, and swelling) as parameters to grade severity of inflammation . However, in the case of papain‐CL model, it was difficult to obtain reliable clinical scores because the inflammation of this model did not highly depend on immediate hypersensitivity reactions.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our results showed the indispensable roles of IL‐33 and TSLP in the eosinophil infiltration induced by papain‐CL, this result is consistent with previous reports showing attenuated papain‐induced allergic airway inflammation in IL‐33 KO mice , and reduced papain‐induced allergic inflammation in the lung of TSLPR KO mice . In the case of ragweed induced experimental allergic conjunctivitis, we evaluated clinical scores (lid edema, conjunctival hyperemia, and swelling) as parameters to grade severity of inflammation . However, in the case of papain‐CL model, it was difficult to obtain reliable clinical scores because the inflammation of this model did not highly depend on immediate hypersensitivity reactions.…”
Section: Discussionsupporting
confidence: 91%
“…The cytokines are produced and released from epithelial cells in response to allergens, parasites, and tissue damage. Recently, we investigated the roles of type 2 immune response-initiating cytokines in ragweed-induced experimental allergic conjunctivitis (ragweed EAC) using IL-33-, IL-25-, and TSLP receptor (TSLPR)-knockout (KO) mice [4]. We found attenuated eosinophil infiltration and reduced Th2 cytokine (il4, il5, and il13) mRNA expression in the ragweed EAC model using IL-33 KO mice, suggesting an indispensable role for IL-33 in the pathophysiology of ragweed EAC mostly driven by adaptive immune responses [5].…”
Section: Introductionmentioning
confidence: 99%
“…IL-33 has been now recognized to trigger asthma, rhinitis, atopic dermatitis and allergic conjunctivitis68910. Recently, the role of IL-33 in initiating allergic inflammation has been investigated in SRW pollen-induced mouse models of allergic conjunctivitis1112 or allergic rhinitis13. The studies of Asada and Haenuki were carried out using IL-33 knockout mice and showed the pathophysiological roles of IL-33 in SRW induced allergic disease models in mouse1213.…”
mentioning
confidence: 99%
“…Recently, the role of IL-33 in initiating allergic inflammation has been investigated in SRW pollen-induced mouse models of allergic conjunctivitis1112 or allergic rhinitis13. The studies of Asada and Haenuki were carried out using IL-33 knockout mice and showed the pathophysiological roles of IL-33 in SRW induced allergic disease models in mouse1213. However, it remains unknown whether and how IL-33 is induced by pollen allergens via TLR4-dependent innate immunity pathways.…”
mentioning
confidence: 99%
“…After ragweed pollen administration, IL-33 is released and lead to the infiltration of eosinophils and CD4 + T cells with activated ST2 on the surface in conjunctival stroma [ 110 ]. These activations are obviously reduced in IL-33-knockout mice [ 111 ]. Furthermore, pollen-induced IL-33 production is decreased in TLR4-deficient mice and is blocked by TLR4 antibody in vitro [ 112 ].…”
Section: The Role Of Il-33 In Allergic Diseasesmentioning
confidence: 99%